The Glutamate and Chloride Permeation Pathways Are Colocalized in Individual Neuronal Glutamate Transporter Subunits - Leary, Gregory P. (J Neurosci, 2007)
Glutamate transporters have a homotrimeric subunit structure with a large central water-filled cavity that extends partially into the plane of the lipid bilayer (Yernool et al., 2004). In addition to uptake of glutamate, the transporters also mediate a chloride conductance that is increased in the presence of substrate. Whether the chloride channel is located in the central pore of the trimer or within the individual subunits has been controversial. We find that coexpression of wild-type neuronal glutamate transporter EAAT3 subunits with subunits mutated at R447, a residue governing substrate selectivity (Bendahan et al., 2000), results in transport activity consistent with two distinct noninteracting populations of transporters, in agreement with previous work suggesting that each subunit operates independently to transport substrate (Awes et al., 2004; Grewer et al., 2005; Koch and Larsson, 2005). In wild-type homotrimeric transporters, the glutamate concentration dependence of the anion conductance and the kinetics of glutamate flux were isolated and measured, and the anion channel activation was fitted to analytical expressions corresponding to (1) a central pore gated by binding to one or more subunits and (2) a channel pore in each subunit. The data indicate that glutamate-binding sites, transport pathways, and chloride channels reside in individual subunits in a trimer and function independently.